Patient pathways in primary health care – an interview study across various health care personnel in a Canadian and a Norwegian county - Vivian Nystrøm; Arto Ohinmaa; Ann-Chatrin Linqvist Leonardsen (BMC Health Services Research)
Abstract Background Due to demographic changes in the Western world governments emphasize the need for viable solutions, e.g. through decentralization of specialist health care services and better coordination within and between health care services. Both Norway and Canada have been through health care reforms and initiatives aiming to improve continuity and coordination of services. Organizational change to primary care in both countries encompasses both team-based service delivery involving allied health professionals, and new blended payment models. The objective of this study was to explore patient pathways in primary healthcare from various health personnel’s perspectives, and across various primary care organizations in Norway and Canada. Methods The study had a qualitative design, including interviews with physicians, nurses and managers (n = 19) in primary care, from a county in Norway and a region in Canada. Data were analyzed with a thematic approach, in line with recommendations from Braun & Clarke. Results Three themes were identified: 1) Structural challenges, 2) Towards a more specialized primary health care and 3) Dedication could improve continuity. Findings indicate that coordinating health care services was assumed difficult due to different health care levels, funding systems, managements, electronic record systems and organizations. Hospitals were assumed more task oriented, while primary health care services were considered more care oriented, and this challenged the coordination across organizations. Primary care services were perceived to be more and more specialized, also representing a threat for coordination and continuity. Health care personnel in both countries perceived that dedicated personnel for each patient could improve information flow and continuity across services. Conclusions Achieving continuity and coordination of health care services seems challenging. Integration strategies seem essential for reducing silo thinking and fragmentation of health care services.